THE STORY BEHIND “GULSHANUL MULUK” BY AMIR SHAHMUROD: AN IN-DEPTH ANALYSIS - Hamroyev Asliddin Umed ugli (Journal of Learning on History and Social Sciences, 2024)
This article describes research conducted on the memoirs of Muhammad Yaqub Bukhari, the author of Gulshanul Mulk, which is considered one of the most important historical sources of that time, regarding Amir Shahmurad, one of the prominent noblemen. Additionally, the article discusses the significance of “Gulshanul Muluk” in studying the history of the Mangite period, providing valuable insights into the rulers of that era from a historical perspective